2015
DOI: 10.7554/elife.07343
|View full text |Cite
|
Sign up to set email alerts
|

Logics and properties of a genetic regulatory program that drives embryonic muscle development in an echinoderm

Abstract: Evolutionary origin of muscle is a central question when discussing mesoderm evolution. Developmental mechanisms underlying somatic muscle development have mostly been studied in vertebrates and fly where multiple signals and hierarchic genetic regulatory cascades selectively specify myoblasts from a pool of naive mesodermal progenitors. However, due to the increased organismic complexity and distant phylogenetic position of the two systems, a general mechanistic understanding of myogenesis is still lacking. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 91 publications
2
43
0
Order By: Relevance
“…In all experiments, as a negative control, embryos were injected with 100 µM of the standard control MASO (oligo end modified with 3′-Carboxyfluorescein, control-fluo MASO, Gene Tools) at equal or greater concentration and compared side-by-side with uninjected and MASO embryos. As for previous experiments (Andrikou et al, 2015) no delay of development or abnormal morphology was observed at any stage in the control-fluo MASO injected embryos (Figure S1). For mRNA injection, Capped synthetic mRNA was made with T3 RNA polymerase using mMESSAGE mMACHINE Kit (Ambion, Austin, USA), subsequently treating the RNA product with DNase I to remove DNA template.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…In all experiments, as a negative control, embryos were injected with 100 µM of the standard control MASO (oligo end modified with 3′-Carboxyfluorescein, control-fluo MASO, Gene Tools) at equal or greater concentration and compared side-by-side with uninjected and MASO embryos. As for previous experiments (Andrikou et al, 2015) no delay of development or abnormal morphology was observed at any stage in the control-fluo MASO injected embryos (Figure S1). For mRNA injection, Capped synthetic mRNA was made with T3 RNA polymerase using mMESSAGE mMACHINE Kit (Ambion, Austin, USA), subsequently treating the RNA product with DNase I to remove DNA template.…”
Section: Methodssupporting
confidence: 84%
“…Moreover, the same antibody, used in immunohistochemistry assays, identifies the phosphorylated protein in all nuclei of the early blastula (Fig. 4E), while it appears confined at the tip of archenteron of the early gastrula (Andrikou et al, 2015), a region in which the activated form of ERK kinase is strongly expressed (Fernandez-Serra et al, 2004; Rottinger et al, 2004). …”
Section: Resultsmentioning
confidence: 96%
“…The data presented on O-A polarity in the NSM of Et suggest that multiple regulatory domains unfold at and around the tip of the archenteron as gastrulation proceeds, as is also the case in euechinoids (98), and that these embryonic domains have diverged markedly since the divergence of the two modern echinoid clades.…”
Section: Divergent Regulatory Linkages In the Evolution Of Echinoid Ementioning
confidence: 97%
“…The set of Pax, bHLH, Six, Eya, Dach, and MADS transcription factors involved in myogenesis is conserved throughout Bilateria. However, the hierarchy of gene interactions has been reshuffled in some bilaterian groups, and some key myogenic factors were lost in some lineages during evolution, such as Pax3/7 in sea urchins (Andrikou et al, 2015). The general consensus is that MRFs play a crucial role in bilaterian muscle specification and differentiation (reviewed in Bentzinger et al, 2012; Andrikou and Arnone, 2015).…”
Section: Molecular Characterization Of Muscles In Cnidariansmentioning
confidence: 99%